PRO‐C3, a Serological Marker of Fibrosis, During Childhood and Correlations With Fibrosis in Pediatric NAFLD. Issue 11 (8th July 2021) - Cohen, Catherine C.; Castillo‐Leon, Eduardo; Farris, Alton B.; Caltharp, Shelley A.; Cleeton, Rebecca L.; Sinclair, Elizabeth M.; Shevell, Diane E.; Karsdal, Morten A.; Nielsen, Mette Juul Fisker; Leeming, Diana J.; Vos, Miriam B.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease in children and may lead to cirrhosis requiring liver transplant. Thus, prompt diagnosis of advanced fibrosis is essential. Our objectives were to examine PRO‐C3 (a neo‐epitope pro‐peptide of type III collagen formation) levels across childhood/adolescence and associations with advanced fibrosis in pediatric NAFLD. This cross‐sectional study included 88 children and adolescents with biopsy‐proven NAFLD (mean age: 13.9 ± 2.9 years, 71% male) and 65 healthy participants (11.8 ± 4.5 years, 38% male). PRO‐C3, and the bone remodeling biomarkers C‐terminal telopeptide of type I collagen (CTX‐I; bone resorption) and osteocalcin (N‐MID; bone formation), were measured in serum by enzyme‐linked immunosorbent assay. Fibrosis was assessed by liver biopsy in participants with NAFLD, who were categorized as having advanced (Ishak score ≥ 3) or none/mild fibrosis (Ishak score ≤ 2). Overall, PRO‐C3 was similar in participants with NAFLD (median [interquartile range]: 20.6 [15.8, 25.9] ng/mL) versus healthy participants (19.0 [13.8, 26.0] ng/mL), but was significantly lower in older adolescents ≥ 15 years old (16.4 [13.0, 21.2] ng/mL) compared with children ≤ 10 years old (22.9 [18.1, 28.4] ng/mL; P  < 0.001) or 11‐14 years old (22.4 [18.3, 31.2] ng/mL; P  < 0.001). PRO‐C3 was also directly correlated with levels of CTX‐I and N‐MID ( r  = 0.64 and r  = 0.62, respectively; both P  < 0.001). Among participants with NAFLD, PRO‐C3 was higher in those with advanced fibrosis (median [IQR]: 28.5 [21.6, 37.6]) compared with none/mild fibrosis (20.3 [18.2, 22.8]; P  = 0.020) in models adjusted for age, sex, and body mass index z ‐score. However, associations were attenuated after additionally adjusting for bone‐remodeling CTX‐I ( P  = 0.09) or N‐MID ( P  = 0.08). Conclusion: Collectively, these findings show that PRO‐C3 levels are higher in children with advanced fibrosis in NAFLD, but are also influenced by age and pubertal growth spurt, assessed by bone remodeling biomarkers, and therefore may not be a reliable biomarker for liver fibrosis in pediatric NAFLD until late adolescence.